Work Performance Of The Academic Staff In Community Outreach At The United Colleges Of Rattanakosin, Thailand - Pothimamaka, Jittrarat (1994)

(untitled)
The major objective of this study was to identify the predicting factors and discriminating variables of community outreach work performance of academic staff a t the United Colleges of Rattanakosin in Thailand. A survey with structured, self-administered questionnaires was employed to a random sample of 304 academic staff members from four faculties representing each of the six teachers colleges of the United Colleges of Rattanakosin. Descriptive and inferential statistical procedures,namely,frequency,factor analysis,F - test, Pearson correlation,multiple regression,and discriminant analysis were used to analyze the data . More than three quarters of the respondents were females, with an average age of 45 year sand teaching experience of 21 years.Most of the respondents were instructors with master's degree holders.